Cine and late gadolinium enhancement MRI registration and automated myocardial infarct heterogeneity quantification. Issue 5 (23rd November 2020) - Guo, Fumin; Krahn, Philippa R. P.; Escartin, Terenz; Roifman, Idan; Wright, Graham
Abstract : Purpose: To develop an approach for automated quantification of myocardial infarct heterogeneity in late gadolinium enhancement (LGE) cardiac MRI. Methods: We acquired 2D short‐axis cine and 3D LGE in 10 pigs with myocardial infarct. The 2D cine myocardium was segmented and registered to the LGE images. LGE image signal intensities within the warped cine myocardium masks were analyzed to determine the thresholds of infarct core (IC) and gray zone (GZ) for the standard‐deviation (SD) and full‐width‐at‐halfmaximum (FWHM) methods. The initial IC, GZ, and IC + GZ segmentations were postprocessed using a normalized cut approach. Cine segmentation and cine‐LGE registration accuracies were evaluated using dice similarity coefficient and average symmetric surface distance. Automated IC, GZ, and IC + GZ volumes were compared with manual results using Pearson correlation coefficient ( r ), Bland‐Altman analyses, and intraclass correlation coefficient. Results: For n = 87 slices containing scar, we achieved cine segmentation dice similarity coefficient = 0.87 ± 0.12, average symmetric surface distance = 0.94 ± 0.74 mm (epicardium), and 1.03 ± 0.82 mm (endocardium) in the scar region. For cine‐LGE registration, dice similarity coefficient was 0.90 ± 0.06 and average symmetric surface distance was 0.72 ± 0.39 mm (epicardium) and 0.86 ± 0.53 mm (endocardium) in the scar region. For both SD and FWHM methods, automated IC, GZ, and IC + GZ volumes were strongly ( r > 0.70) correlated with manual measurements, and the correlations were not significantly different from interobserver correlations ( P > .05). The agreement between automated and manual scar volumes (intraclass correlation coefficient = 0.85‐0.96) was similar to that between two observers (intraclass correlation coefficient = 0.81‐0.99); automated scar segmentation errors were not significantly different from interobserver segmentation differences ( P > .05). Conclusions: Our approach provides fully automated cine‐LGE MRI registration and LGE myocardial infarct heterogeneity quantification in preclinical studies.